PENERAPAN MODEL PEMBELAJARAN LEARNING STARTS WITH A QUESTION UNTUK MENINGKATKAN HASIL BELAJAR IPA TEMA EKOSISTEM SISWA KELAS V UPT. SD NEGERI 22 BARINGIN - Rosda, Eni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The right learning model is needed to achieve an active learning process, generally teachers at UPT. SD Negeri 22 Baringin is not right to use a learning model that should be in accordance with the teaching material. So that students in the class often feel bored and less enthusiastic about learning, which makes the classroom atmosphere passive and few students want to ask the teacher even though the material being taught has not been understood so that it affects learning outcomes. Given the problems that lead to unsatisfactory student learning outcomes, researchers are very careful in applying the learning model. Researchers try to use the learning model learning starts with a question. This study aims to determine teacher activities, student activities and student learning outcomes through the application of the learning model learning starts with a question. This research is a Classroom Action Research with the research subjects of class V UPT students. SD Negeri 22 Baringin. This research was conducted in two cycles, each of which included planning, implementing, observing and reflecting. Data obtained through research instruments, observation sheets, tests, and processed using a percentage formula. Based on the research results, it is known that: (1) Teacher activity with the application of the learning model starts with a question increased from cycle I only at 66.67% increased in cycle II to 83.33%, (2) Student activity in cycle I was only 69.74% increase in cycle II to 82.95%, (3) Classical student learning outcomes in cycle I only 65% increase in cycle II to 85% this means that most students complete their learning by applying the learning model learning starts with a question on the material on the relationship between living things in the ecosystem in class V UPT. SD Negeri 22 Baringin.